Green Constitution: Strengthening Environment Principle in the Act of 1945 - NAIBORHU, Netty S.R. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.9.5(29).16, 2019)
Environmental issues should not be placed on one side, namely the government (legislative, executive and judicative), but all components of the existing layer in a country must be able to interpret the green constitution in the hearts of each. Green constitution as the idea of constitutionalizing the norm of environmental law into the constitution by raising the draft of environmental protection norms to the constitution level. Approach method used in this research using a normative juridical approach with the focus related to the green constitution as reinforcement of environmental principles in the Constitution with data obtained and analyzed by using a qualitative normative method. This constitutionalization can be grouped into three types. First, formal constitutionalization. This group has a style in which the constitutionalization of environmental policy is carried out by putting it in a formal form on the environment and ideas of sustainable development; Secondly, substantial Constitutionalization. This model is interpreted as a practice of constitutionalization that is not only limited to formal but substantially. As for a reason, that environmental policy becomes the spirit (spirit) of the constitution in a country, Third, structural constitutionalization. This model is an extreme ending which changes the environmental paradigm of the object into the subject of human rights so that the environment can be viewed as a separate legal subject structure beside the human subject.